1992
DOI: 10.1152/jappl.1992.72.6.2188
|View full text |Cite
|
Sign up to set email alerts
|

Endurance training amplifies the pulsatile release of growth hormone: effects of training intensity

Abstract: The effects of intensity of run training on the pulsatile release of growth hormone (GH) were investigated in 21 eumenorrheic untrained women. The O2 consumption (VO2) at the lactate threshold (LT); fixed blood lactate concentrations (FBLC) of 2.0, 2.5, and 4.0 mM; peak VO2; maximal VO2; body composition; and pulsatile release of GH were measured. Subjects in both the at-lactate threshold (/LT, n = 9) and above-lactate threshold (greater than LT, n = 7) training groups increased VO2 at LT and FBLC of 2.0, 2.5,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
79
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(90 citation statements)
references
References 28 publications
9
79
0
2
Order By: Relevance
“…The consistent finding among previously published studies is that exercise, although a potent stimulus for GH release immediately during and after the bout, does not appear to affect the number of GH peaks in the several hours following the exercise (9,14,19,26). Consistent with the results of the Pulsar analysis previously published (14), cluster analysis indicated that the number, duration, and interval between GH concentration (A and B, bottom).…”
Section: Discussionsupporting
confidence: 90%
“…The consistent finding among previously published studies is that exercise, although a potent stimulus for GH release immediately during and after the bout, does not appear to affect the number of GH peaks in the several hours following the exercise (9,14,19,26). Consistent with the results of the Pulsar analysis previously published (14), cluster analysis indicated that the number, duration, and interval between GH concentration (A and B, bottom).…”
Section: Discussionsupporting
confidence: 90%
“…More importantly, GH is a target for physical exercise; it is well known that a linear dose-response relationship exists between exercise intensity and the GH secretory pattern in healthy individuals (10)(11)(12)(13)(14). This is suggested to be an important factor because of the potent lipolytic effect of GH, which further increases energy expenditure and prevents obesity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Chronic aerobic training has been shown to increase GH secretion and amplify pulsatile release of GH at rest in women if some of their training occurred at intensities above lactate threshold (39). The women in this study trained at intensities below lactate threshold for both aerobic and resistance exercise, which may have contributed to a lack of change in basal GH concentration.…”
Section: Discussionmentioning
confidence: 89%